Advancing microbiota therapeutics: the role of synthetic biology in engineering microbial communities for precision medicine - Nazir, Asiya; Hussain, Fathima Hasnain Nadeem; Raza, Afsheen (Frontiers in Bioengineering and Biotechnology, 2024)
Over recent years, studies on microbiota research and synthetic biology have explored novel approaches microbial manipulation for therapeutic purposes. However, fragmented information is available on this aspect with key insights scattered across various disciplines such as molecular biology, genetics, bioengineering, and medicine. This review aims to the transformative potential of synthetic biology in advancing microbiome research and therapies, with significant implications for healthcare, agriculture, and environmental sustainability. By merging computer science, engineering, and biology, synthetic biology allows for precise design and modification of biological systems via cutting edge technologies like CRISPR/Cas9 gene editing, metabolic engineering, and synthetic oligonucleotide synthesis, thus paving the way for targeted treatments such as personalized probiotics and engineered microorganisms.The review will also highlight the vital role of gut microbiota in disorders caused by its dysbiosis and suggesting microbiota-based therapies and innovations such as biosensors for real-time gut health monitoring, non-invasive diagnostic tools, and automated bio foundries for better outcomes. Moreover, challenges including genetic stability, environmental safety, and robust regulatory frameworks will be discussed to understand the importance of ongoing research to ensure safe and effective microbiome interventions